1994
DOI: 10.1152/ajpgi.1994.267.3.g423
|View full text |Cite
|
Sign up to set email alerts
|

Rat parietal cell receptors for GLP-1-(7-36) amide: northern blot, cross-linking, and radioligand binding

Abstract: The intestinal peptide hormone glucagon-like peptide-1 (GLP-1) (7-36) amide is a potent stimulus of H+ production in isolated rat parietal cells, suggesting the presence of specific GLP-1-receptors on this cell type. Our aim was to characterize these receptors. Enzymatically isolated rat gastric mucosal cells (F0) were fractionated by counterflow elutriation, resulting in five fractions (F1-F5) according to increasing cell diameter and parietal cell content (3, 5, 4, 27, 81%). Additional density gradient centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 0 publications
2
26
1
1
Order By: Relevance
“…Using a GLP-1R antibody and immunohistochemistry, Kedees et al (28) reported GLP-1R expression in the intestinal mucosa, enteric nervous system, and Paneth cells, whereas studies using the GLP-1R promoter to direct expression of a fluorescent reporter protein localized intestinal GLP-1R expression to enteric neurons (23). GLP-1Rs have also been localized to gastric parietal cells in rats (29) and in the Brunner's gland of the duodenum, parietal cells and smooth muscle cells in the gastric muscularis externa, and myenteric plexus neurons throughout the primate small and large bowel (30). Given the lack of specificity of the majority of commercially available GLP-1R antibodies and existing discrepancies in studies reporting sites of intestinal GLP-1R expression, we initiated studies to localize the sites of endogenous GLP-1R mRNA expression in the murine gut.…”
Section: Discussionmentioning
confidence: 99%
“…Using a GLP-1R antibody and immunohistochemistry, Kedees et al (28) reported GLP-1R expression in the intestinal mucosa, enteric nervous system, and Paneth cells, whereas studies using the GLP-1R promoter to direct expression of a fluorescent reporter protein localized intestinal GLP-1R expression to enteric neurons (23). GLP-1Rs have also been localized to gastric parietal cells in rats (29) and in the Brunner's gland of the duodenum, parietal cells and smooth muscle cells in the gastric muscularis externa, and myenteric plexus neurons throughout the primate small and large bowel (30). Given the lack of specificity of the majority of commercially available GLP-1R antibodies and existing discrepancies in studies reporting sites of intestinal GLP-1R expression, we initiated studies to localize the sites of endogenous GLP-1R mRNA expression in the murine gut.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 receptors are expressed on gastric parietal cells (7,41,55), which suggests that GLP-1R might inhibit gastric emptying and/or gastric acid secretion through a direct Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling in beta cells is discussed below. The receptor is widely distributed in pancreatic islets, brain, heart, kidney, and the gastrointestinal tract (5, 28, 33, 322, 323) including the stomach, where the receptor is expressed on the parietal cells (262). Its function is not known for all these locations (see below).…”
Section: Effects Of Glucagon-like Peptide 1 a The Glp-1 Receptormentioning
confidence: 99%